DETERMINANTS OF CREDIT RISK - Riyazahmed, K.; Baranwal, Gunja (International Journal of Accounting & Finance Review, 2021)
This study aims to empirically examine the impact of managerial effectiveness on the credit risk of the Indian public and private sector banks. We consider the return on assets as a proxy for managerial effectiveness and gross non-performing assets (GNPA) to total advances as a proxy for credit risk. The study uses fixed effects and dynamic panel data models to examine the impact. The econometric model estimations suggest a negative impact of return on assets on credit risk. Further, we analyze the impact of return on assets by the information of microeconomic and macro-economic variables in dynamic generalized methods of moments (GMM) approach. The results remain the same after using dynamic GMM modelled with lagged credit risk and lagged return on assets. Further, the effect of macroeconomic variables such as repo rate and reverse repo rate confirms the theory. Heterogeneity checks at regions and sector levels substantiate the robustness of results. JEL Classification Codes: G20, G21.